2023
DOI: 10.1186/s12916-023-02822-w
|View full text |Cite
|
Sign up to set email alerts
|

Light at night and cause-specific mortality risk in Mainland China: a nationwide observational study

Abstract: Background While epidemiological studies have found correlations between light at night (LAN) and health effects, none has so far investigated the impacts of LAN on population mortality yet. We aimed to estimate the relative risk for mortality from exposure to LAN in Mainland China. Methods This time-stratified case-crossover nationwide study used NPP-VIIRS to obtain daily LAN data of Mainland China between 2015 and 2019. The daily mortality data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…We calculated an objective measure of mean OALAN, expressed in units of radiance as nanowatts per centimeter squared per steradian, for each geocoded address for the years 2008 to 2009 using the National Geophysical Data Center’s latest radiance-calibrated light-at-night data (Figure 1). Such data have been proposed as a reliable proxy measure for relative levels of nighttime illumination at ground level and have been used recently to assess the effects of light pollution on various comorbidities …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated an objective measure of mean OALAN, expressed in units of radiance as nanowatts per centimeter squared per steradian, for each geocoded address for the years 2008 to 2009 using the National Geophysical Data Center’s latest radiance-calibrated light-at-night data (Figure 1). Such data have been proposed as a reliable proxy measure for relative levels of nighttime illumination at ground level and have been used recently to assess the effects of light pollution on various comorbidities …”
Section: Methodsmentioning
confidence: 99%
“…Such data have been proposed as a reliable proxy measure for relative levels of nighttime illumination at ground level and have been used recently to assess the effects of light pollution on various comorbidities. 15 , 21 , 33 …”
Section: Methodsmentioning
confidence: 99%
“…To date, two types of ALAN satellite data were utilized in human health research, including the Operational Linescan System of Defense Meteorological Satellite Program (OLS-DMSP) and the Suomi National Polar-Orbiting Partnership Visible Infrared Imaging Radiometer Suite (NPP-VIIRS) (24,25). DMSP-OLS was launched in 1992, with a spatial resolution of 1 km × 1 km for its data products (26).…”
Section: Assessment Of Outdoor Alanmentioning
confidence: 99%
“…In particular, one previous investigation suggested a higher risk of mild cognitive impairment in Chinese veterans exposed to excessive outdoor LAN [ 32 ]. Similarly, another study suggested a positive relation between LAN exposure and all-cause mortality in China, with the strongest effect on neuron system disease, although no specific assessment of dementia was reported [ 33 ].…”
Section: Introductionmentioning
confidence: 99%